2021
DOI: 10.7150/ijbs.63125
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Validation of Nitroxoline as a Novel STAT3 Inhibitor in Drug-resistant Urothelial Bladder Cancer

Abstract: Repeated cycles of first-line chemotherapy drugs such as doxorubicin (DOX) and cisplatin (CIS) trigger frequent chemoresistance in recurrent urothelial bladder cancer (UBC). Nitroxoline (NTX), an antibiotic to treat urinary tract infections, has been recently repurposed for cancer treatment. Here we aimed to investigate whether NTX suppresses drug-resistant UBC and its molecular mechanism. The drug-resistant cell lines T24/DOX and T24/CIS were established by continual exposure of parental cell line T24 to DOX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 46 publications
0
14
0
4
Order By: Relevance
“…Nitroksolina (NTX) jest to chemioterapeutyk o powszechnie znanym działaniu przeciwbakteryjnym, przeciwgrzybiczym, który stosowany jest w Europie od kilku dekad. Największe zastosowanie znalazła w leczeniu zakażeń dróg moczowych [1]. Częstość występowania uropatogenów wieloopornych (MDR), czyli bakterii opornych na 1 antybiotyk z co najmniej trzech różnych klas antybiotyków wzrasta na całym świecie zarówno u pacjentów leczonych w warunkach ambulatoryjnych, jak i szpitalnych na zakażenie układu moczowego (UTIs).…”
Section: Wprowadzenieunclassified
See 3 more Smart Citations
“…Nitroksolina (NTX) jest to chemioterapeutyk o powszechnie znanym działaniu przeciwbakteryjnym, przeciwgrzybiczym, który stosowany jest w Europie od kilku dekad. Największe zastosowanie znalazła w leczeniu zakażeń dróg moczowych [1]. Częstość występowania uropatogenów wieloopornych (MDR), czyli bakterii opornych na 1 antybiotyk z co najmniej trzech różnych klas antybiotyków wzrasta na całym świecie zarówno u pacjentów leczonych w warunkach ambulatoryjnych, jak i szpitalnych na zakażenie układu moczowego (UTIs).…”
Section: Wprowadzenieunclassified
“…Udowodniono, że nitroksolina ma szerokie działanie przeciwbakteryjne wobec opornych szczepów wielu bakterii [9,20]. Na przestrzeni ostatnich lat stwierdzono, że jest skuteczna również w walce z kilkoma nowotworami [1]. Kilka badań doniosło, że NTX może być potencjalnym lekiem przeciwnowotworowym w leczeniu raka pęcherza moczowego, raka prostaty, glejaka, raka trzustki i innych [2].…”
Section: Wprowadzenieunclassified
See 2 more Smart Citations
“…Recently, several studies have reported that nitroxoline may be a potential antineoplastic drug in bladder cancer, myeloma, glioma, pancreatic cancer, prostate cancer and so on 7 - 11 . Our recent research suggested that nitroxoline, as a novel STAT3 inhibitor, could induce P-gp reversal, G0/G1 arrest, and apoptosis in drug-resistant urothelial bladder cancer 12 . Notably, completed multicenter phase II clinical trials have demonstrated the efficacy and safety of nitroxolines in chemotherapy/BCG instillation unresponsive high-risk NMIBC patients, with significantly better clinical efficacy than the currently clinically used bladder instillation chemotherapeutic agents (e.g., mitomycin) and immunologic agents (e.g., BCG).…”
Section: Introductionmentioning
confidence: 99%